Analysis of coupling effect between metamolecules in toroidal metamaterials. (19th July 2021) - Sun, Bo; Yu, Yingying; Wang, Hong; Zhu, Hongyu; Yang, Wenxing
Abstract: Anti-parallel aligned toroidal dipole arrays can be excited in metamaterials, and the total energy can be regulated by producing an antiparallel coupling effect between the toroidal dipoles. In this study, numerical and experimental analyses are performed on the coupling of toroidal moments in metamaterials. We introduce a new reverse toroidal dipole by altering the distance between metamolecules, and the correlation between the antiparallel coupling and the period is analyzed. The geometrical parameters of the period are found to play significant roles in altering the resonance response. When the intensities of two opposite dipoles are similar, the toroidal interaction energy reaches a maximum and increases the total energy, which results in an increase in the Q -factor. These results provide new insights regarding toroidal metamaterials with nontrivial yet controllable responses and for developing toroidal-based plasmonic applications.